Adonis amurensis Is a Promising Alternative to Haematococcus as a Resource for Natural Esterified (3S,3′S)-Astaxanthin Production - Yongfu Li; Fengying Gong; Shuju Guo; Wenjie Yu; Jianguo Liu (Plants, 2021)
Astaxanthin (AST) characteristics and pigment productivity of Adonis amurensis, one of the few AST-producing higher plants, have not yet been studied extensively. In this study, the geometrical and optical isomers of AST in different parts of the A. amurensis flower were determined in detail, followed by a separation of the all-trans AST using HPLC chromatography. AST extracted from the flower accounted for 1.31% of the dry weight (dw) and mainly existed in the di-esterified form (>86.5%). The highest concentration was found in the upper red part of the petal (3.31% dw). One optical isomer (3S, 3′S) of AST, with five geometrical isomers (all-trans, 9-cis, 13-cis, 15-cis, and di-cis) were observed in all parts of the flower. All-trans AST was the predominant geometrical isomer accounting for 72.5% of the total content of geometric isomers in total flower, followed by the 13-cis, and 9-cis isomers. The all-trans AST isomer was also isolated, and then purified by HPLC from the crude oily flower extract, with a 21.5% recovery yield. The cis-AST extracted from the combined androecium and gynoecium gives a very strong absorption in the UVA region due to a high level of cis, especially di-cis, isomers, suggesting a prospective use in the preparation of anti-ultraviolet agents. The production cost of AST from Adonis flowers can be as low as €388–393/kg. These observations together with other factors such as the low technology requirement for plant culturing and harvesting suggest Adonis has great potential as a resource for natural esterified (3S,3′S)-AST production when compared with Haematococcus culturing.